1998
DOI: 10.1152/jappl.1998.85.5.1693
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H3 activation depresses cardiac function in experimental sepsis

Abstract: In the heart, histamine (H3) receptors may function as inhibitory presynaptic receptors that decrease adrenergic norepinephrine release in conditions of enhanced sympathetic neural activity. We hypothesized that H3-receptor blockade might improve cardiovascular function in sepsis. In a canine model of Escherichia coli sepsis, we found that H3-receptor blockade increased cardiac output (3.6 to 5.3 l/min, P< 0.05), systemic blood pressure (mean 76 to 96 mmHg, P < 0.05), and left ventricular contractility c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…In the analysis, stroke work (SW) was our primary index of cardiac performance and the primary hemodynamic end point chosen in the in vivo studies (17,18) (see Discussion). At constant preload, SW reflects both the decreases in afterload and the changes in contractile function that accompany sepsis.…”
Section: In Vivo Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analysis, stroke work (SW) was our primary index of cardiac performance and the primary hemodynamic end point chosen in the in vivo studies (17,18) (see Discussion). At constant preload, SW reflects both the decreases in afterload and the changes in contractile function that accompany sepsis.…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…In the pretreatment study, TAC was given before the bacteria were infused. Based on previous studies, it takes approximately 3-4 hrs of constant bacteremia for myocardial depression to develop in this model (12,18). A 3-to 5-hr course of bacteremia was therefore considered necessary to determine whether TAC could block the decline in SW observed at this interval.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Furthermore, in rat mesenteric arteries the overproduction of both nitric oxide and prostanoids by endothelium was shown to reduce the electrically evoked contraction after administration of LPS (Fatehi-Hassanabad et al, 1995). Moreover, Li et al (1998) and Cheng et al (2002) demonstrated that the activation of presynaptic histamine H 3 receptors during sepsis resulted in the depression of left ventricular contractility in canine heart, hence contributing to the cardiovascular collapse.…”
Section: Introductionmentioning
confidence: 95%
“…Such an effect might have been expected on the basis of our previous report showing the occurrence of H 3 receptors on the sympathetic innervation of rat resistance vessels, which were tonically activated by endogenous histamine . Moreover, the activation of presynaptic histamine H 3 receptors during sepsis resulted in the depression of left ventricular contractility in canine heart (Li et al, 1998) and contributed to the cardiovascular collapse in dogs (Cheng et al, 2002). As the dose of 100 nmol kg À1 of clobenpropit antagonized the effects of the selective H 3 receptor agonists R-a-methylhistamine and imetit in pithed rats , the lack of its activity in the present study may mean that histamine H 3 receptors are not active in the initial phase of septic shock, at least not of rats.…”
mentioning
confidence: 97%
“…Histamine H 3 receptors are located presynaptically on postganglionic sympathetic noradrenergic nerves, including sympathetics innervating the heart and blood vessels (Imamura et al, 1995;Li et al, 1998;Malinowska et al, 1998). The presence of functional H 3 receptors in the cardiovascular system has been demonstrated in vitro in human, guinea pig, rabbit and rat effector systems, and in vivo in the rat, guinea pig and dog (Malinowska et al, 1998).…”
Section: Introductionmentioning
confidence: 99%